2009
DOI: 10.2196/jmir.1179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Active-Online, an Individually Tailored Physical Activity Intervention, in a Real-Life Setting: Randomized Controlled Trial

Abstract: BackgroundEffective interventions are needed to reduce the chronic disease epidemic. The Internet has the potential to provide large populations with individual advice at relatively low cost.ObjectiveThe focus of the study was the Web-based tailored physical activity intervention Active-online. The main research questions were (1) How effective is Active-online, compared to a nontailored website, in increasing self-reported and objectively measured physical activity levels in the general population when delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 49 publications
0
87
0
1
Order By: Relevance
“…An extensive body of research has demonstrated that message tailoring (i.e., providing messages that address each individual's specific concerns, beliefs and experiences) is an effective method for increasing compliance with preventive health behaviors, but to our knowledge has never been applied to parental MMR vaccine hesitancy [17][18][19][20] (though some studies suggest a potential role for message framing and/or decision aids in positively influencing parental MMR vaccine decisions, 21,22 and formative studies suggest a benefit to offering different types of educational materials depending on the degree of parental vaccine hesitancy). 23,24 We tested whether an individually-tailored web-based intervention was more effective than a similar-appearing untailored intervention at improving parental MMR vaccination intention among MMR vaccine-hesitant parents.…”
mentioning
confidence: 99%
“…An extensive body of research has demonstrated that message tailoring (i.e., providing messages that address each individual's specific concerns, beliefs and experiences) is an effective method for increasing compliance with preventive health behaviors, but to our knowledge has never been applied to parental MMR vaccine hesitancy [17][18][19][20] (though some studies suggest a potential role for message framing and/or decision aids in positively influencing parental MMR vaccine decisions, 21,22 and formative studies suggest a benefit to offering different types of educational materials depending on the degree of parental vaccine hesitancy). 23,24 We tested whether an individually-tailored web-based intervention was more effective than a similar-appearing untailored intervention at improving parental MMR vaccination intention among MMR vaccine-hesitant parents.…”
mentioning
confidence: 99%
“…These approaches have only partly shown significant increases of daily activity (Carr et al, 2008;Hurling et al, 2007;Wanner et al, 2009), but direct measurements of physical fitness (e.g. aerobic exercise capacity) have not been assessed before.…”
Section: Discussionmentioning
confidence: 99%
“…aerobic exercise capacity) have not been assessed before. Wanner et al (2009) compared a tailored website with different activity modules to a nontailored site offering general information and found an increase in self-reported physical activity in both groups, whereas accelerometer data did not change after intervention. Similar data were obtained by Spittaels et al (2007a) in a workplace setting.…”
Section: Discussionmentioning
confidence: 99%
“…The internet is useful for providing health information to large specific populations (Napolitano and Marcus, 2002;Wanner Martin-Diener, Braun-Fahrlander, Bauer, & Martin, 2009;Yap, Hemmings, & Davis, 2009). Use of the internet and email is increasing among the work-age adult population (Napolitano et al, 2003).…”
Section: Psychologymentioning
confidence: 99%